2018
DOI: 10.1097/lbr.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Cone-Beam CT With Augmented Fluoroscopy Combined With Electromagnetic Navigation Bronchoscopy for Biopsy of Pulmonary Nodules

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
159
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 42 publications
4
159
2
2
Order By: Relevance
“…While the use of intraoperative cone‐beam CT confirmation might mitigate these issues and provide near real‐time confirmatory imaging, access to cone‐beam technology is limited to a handful of expert centres, and dissemination of the technology will likely be slow . Fluoroscopic ENB (F‐ENB, Medtronic, Minneapolis, MN, USA) is a novel technology that uses digital tomosynthesis technology via a conventional fluoroscopy C‐arm to visualize and re‐register the target nodule based on near real‐time imaging to compensate for divergence.…”
Section: Introductionmentioning
confidence: 99%
“…While the use of intraoperative cone‐beam CT confirmation might mitigate these issues and provide near real‐time confirmatory imaging, access to cone‐beam technology is limited to a handful of expert centres, and dissemination of the technology will likely be slow . Fluoroscopic ENB (F‐ENB, Medtronic, Minneapolis, MN, USA) is a novel technology that uses digital tomosynthesis technology via a conventional fluoroscopy C‐arm to visualize and re‐register the target nodule based on near real‐time imaging to compensate for divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Radial endoscopic ultrasound (R-EBUS), fluoroscopy, CT, cone beam CT or a combination of R-EBUS and radiology imaging are used to confirm position prior to sampling. [189][190][191][192][193][194][195][196][197][198] A meta-analysis of R-EBUS showed a pooled sensitivity of 0.72 (95% CI 0.70-0.75). 199 Significant study heterogeneity was noted.…”
Section: Section 6 Diagnostic Methods For Screen-detected Lung Nodulesmentioning
confidence: 99%
“…46 A recent retrospective study of 75 consecutive patients reported an overall diagnostic yield of 83.7%. 47 The median lesion size was 16 mm with a range of 7 to 55 mm. No correlation was detected between diagnostic yield and lesion size, location, and visibility under standard fluoroscopy or the presence of a bronchus sign.…”
Section: Bronchoscopic Transparenchymal Nodule Accessmentioning
confidence: 99%
“…The most recent study by Pritchett et al had a pneumothorax rate of 4%. 47 Radiation exposure was evaluated in a subset of nine patients. The mean effective dose was 2 mSV per CBCT scan.…”
Section: Bronchoscopic Transparenchymal Nodule Accessmentioning
confidence: 99%